2021
DOI: 10.1177/13524585211032510
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid inflammatory profile of cognitive impairment in newly diagnosed multiple sclerosis patients

Abstract: Background: The cerebrospinal fluid (CSF) molecular milieu is a marker of diffuse intrathecal inflammation in the meninges that, in turn, targets the grey matter (GM) in multiple sclerosis (MS). Cognitive impairment (CI) is associated with brain damage in MS and is often present early in people with MS (pwMS). Objective: To investigate whether a specific CSF inflammatory profile is associated with different degrees of CI in newly diagnosed pwMS. Methods: Sixty-nine pwMS and 43 healthy controls (HCs) underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…One subject with detectable CSF CXCL13 versus none among those with undetectable chemokine had also persistence of HIV-associated dementia and spastic tetraparesis with a brain MRI imaging compatible with advanced HIV encephalopathy despite being on effective treatment since more than two years. In multiple sclerosis, which shows several overlaps with HIV-related CNS inflammatory processes (Bonnan et al 2015), CSF CXCL13 has been usually reported as moderately higher (20 pg/mL up to more tha 500 pg/mL) compared to what we measured in our study population (Khademi et al 2011;Alvarez et al 2013;DiSano et al 2020;Pitteri et al 2022). Increased CSF CXCL13 levels have been linked with disease activity, relapse rate, number of brain lesions and unfavourable overall prognosis (Khademi et al 2011;Alvarez et al 2013;DiSano et al 2020).…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…One subject with detectable CSF CXCL13 versus none among those with undetectable chemokine had also persistence of HIV-associated dementia and spastic tetraparesis with a brain MRI imaging compatible with advanced HIV encephalopathy despite being on effective treatment since more than two years. In multiple sclerosis, which shows several overlaps with HIV-related CNS inflammatory processes (Bonnan et al 2015), CSF CXCL13 has been usually reported as moderately higher (20 pg/mL up to more tha 500 pg/mL) compared to what we measured in our study population (Khademi et al 2011;Alvarez et al 2013;DiSano et al 2020;Pitteri et al 2022). Increased CSF CXCL13 levels have been linked with disease activity, relapse rate, number of brain lesions and unfavourable overall prognosis (Khademi et al 2011;Alvarez et al 2013;DiSano et al 2020).…”
Section: Discussionmentioning
confidence: 42%
“…Increased CSF CXCL13 levels have been linked with disease activity, relapse rate, number of brain lesions and unfavourable overall prognosis (Khademi et al 2011;Alvarez et al 2013;DiSano et al 2020). Interestingly, CSF CXCL13 levels were used to discriminate mild from severe cognitive impairment in patients suffering from multiple sclerosis (Pitteri et al 2022). In PLWH, increased intrathecal synthesis has been previously associated with a worse neurocognitive outcome (Bonnan et al 2015;De Almeida et al 2021); herein, we have introduced in this relationship a further piece represented by CSF CXCL13 that could be is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Discussionmentioning
confidence: 99%
“…These follicles might contain the oligoclonal B cell expansions and follicular T H cells that have been identified by singlecell transcriptome analysis in the CSF of patients with MS 134,135 . Levels of C-X-C chemokine ligand 13 (CXCL13), a chemokine that is involved in C-X-C chemokine receptor type 5 (CXCR5)-dependent migration of both B cells and follicular T H cells, correlate with disease severity at the first clinical manifestation of MS 136,137 . In addition, CXCR3 + TBX21 + B cells are abundant in the CNS of patients with MS and might be equipped with superior brain-homing capacity compared with other B cell subsets 138 .…”
Section: Mechanistic Links Between Ebv Infection and Ms The Figure Sh...mentioning
confidence: 99%
“…Even though the meta-analysis did not assess the association of these markers with cognitive performance, some studies have shown that CSF total tau is associated with disability and cognitive impairment [ 53 , 54 ]. In addition to markers of neurodegeneration, inflammatory markers have been also examined, and found to correlate with cognitive impairment in MS [ 92 , 93 ]. How aging and other age-related neurodegenerative processes may play a role in shifting neurodegenerative or inflammatory profiles in the CSF is less clear, and has only been examined by a few [ 94 ].…”
Section: What Are the Neural And Cellular Bases Of Cognitive Aging An...mentioning
confidence: 99%